Study of the fundamental parameters affecting tire models for use in active safety systems in vehicles - Alcázar-Vargas, Manuel Gonzalo (UMA Editorial, 2023)
Active safety in vehicles is a topic of enormous interest to society. In this line, a better knowledge of tire-road interaction broadens the possibilities of improving these safety systems. This thesis analyzes several aspects related to traction, braking and cornering in ground vehicles. Specifically, three papers published in high-impact peer-reviewed journals study each aspect. First, the power transmission in a motorcycle when passing over an uneven road is analyzed. It demonstrates how the motion of the swingarm, engine and wheel are related. This paper proposes an optimized motorbike transmission system design that maximizes the power transmitted to the wheel. For this purpose, genetic algorithms have been used to maximize the distance traveled during a given time. The result is an arrangement of the final drive elements that acts like a mechanical traction control system by delaying and controlling wheel slip under hard acceleration. Second, an algorithm for measuring angular velocities whose delay is known, controllable and independent of speed is developed. This algorithm is compared to current methods of measuring wheel velocities. Results demonstrate the superiority of the proposed approach, providing more robust results compared to its competitors. Third, the influence of various parameters on pure lateral dynamics in tires, both in transient and steady state, is studied. It is observed how temperature dramatically affects the maximum lateral acceleration that a vehicle can experience. The delay in the onset of lateral forces as a function of speed and vertical load is also modeled. These results are of great interest to braking and traction control algorithms since the dynamic response of the tire can be considered to improve the performance of these systems. Finally, the results and conclusions of this work are grouped, as well as future lines of research related to the thesis.
Keywords: Dinámica - Tesis doctorales; Tire Dynamics; Vehicle Dynamics; Multibody Dynamics